SYMBOLS IN JAVANESE MANTRA AJI SEDULURAN: A MAGNIFICENT MORAL VALUE - Teguh Budiharso (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
In this paper, the literal and contextual symbols of Aji Seduluran, a Javanese magical formula were examined. Twelve versions of the ‘mantra’ –Hindu and Islamic- were analyzed by using discourse analysis. The purpose was to understand the meanings of the symbols and put them into the Javanese social and philosophical contexts. The result indicated that the symbols might be classified into three categories: a) symbols of God and gods; b) symbols of human desires; and c)symbols of social tradition. The symbols were also proven to be universal.